2017
DOI: 10.1148/rg.2017160129
|View full text |Cite
|
Sign up to set email alerts
|

Creating Three-dimensional Printed Models of Acetabular Fractures for Use as Educational Tools

Abstract: Acetabular fractures are frequently encountered in some clinical practices, and the precise classification of these fractures greatly influences treatments and outcomes. The authors identified the need for an educational aid when teaching acetabular fracture classifications, given the complex spatial anatomy and the nonintuitive classification system that is commonly used. Three-dimensional ( 3D three-dimensional ) printing is an evolving technique that has applications as an educational aid, providing the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 11 publications
(15 reference statements)
1
16
0
Order By: Relevance
“…However, these models were standard pelvic models on which fracture patterns were created by using an oscillating saw. Last year, Manganaro et al 15 concluded that patient-specific 3D printed models were promising educational tools for teaching and improving learner confidence in using the Judet-Letournel classification system. Furthermore, a couple of case series is available in which it was concluded that 3D printing can be of added value in precontouring plates for acetabular fractures.…”
Section: Introductionmentioning
confidence: 99%
“…However, these models were standard pelvic models on which fracture patterns were created by using an oscillating saw. Last year, Manganaro et al 15 concluded that patient-specific 3D printed models were promising educational tools for teaching and improving learner confidence in using the Judet-Letournel classification system. Furthermore, a couple of case series is available in which it was concluded that 3D printing can be of added value in precontouring plates for acetabular fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate sample production and reliable quantitative analysis of trabeculae between individuals can be realized with the aid of computer tomography and 3D equipment, thus providing a more objective method for better anatomical reduction. 14 Preoperative evaluation and pre-surgical operation using the 3D printing model 15 is conducive to confirming the sequence of reduction and fixation, determining the quality of reduction, shortening the duration of surgery and minimizing the difficulty of surgery. 16 It is also believed by Chen et al that the pre-experiment of the 3D printing template is conducive to the accurate placement of the intramedullary needle during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…3,11 Undeniably, surgeons may determine the approximate location of the fractures based on their previous experience. 11,21 However, it is difficult to obtain the full details of the fracture (the direction and degree of fracture displacement) based on previous techniques. 1,2,4 The recent emergence of 3D printing technology may be beneficial for surgeons.…”
Section: Discussionmentioning
confidence: 99%